Policy of Social Conflict Resolution: Implementation of The Malino Agreement in Maluku - ERNAS, SAIDIN (Universitas Muhammadiyah Yogyakarta, 2012)
Maluku conflict (Ambon) occurred in 1999 to 2003 is one of the most heartbreaking human tragediesin the history of Modern Indonesia. Various attempts have been made by the government to resolve theconflict, including by carrying out Malino Agreement for Maluku. This paper discusses the process ofimplementation of the Malino Agreement and analyzes the impact on the resolution of Malukuconflict. By using methods of descriptive analysis and a qualitative approach, this study can presentsome important findings. First, the Malino Agreement is one strategy (policy) to resolve SARA(racial)conflict well and democratically. It is seen from the atmosphere of the negotiation which is peaceful,honest and democratic. Parties had 11 points of peace agreement due to a strong desire to end theconflict in Maluku. Second, the Malino Agreement has brought positive impacst, i.e lack of escalationof conflict and violence in Maluku, even a year since the Malino Agreement, the peace has beenenforced in Maluku. However, this paper also found that conflict resolution model such as Malinoagreement still needs refinement, as Malino Agreement factually succeeded in pushing the cessation ofconflict, but substantively has not resolved various problems that trigger conflicts in Maluku.